Qualitative Study of the Role of Islamic Law in Shaping Muslim Identity and Business Ethics - Suprijati Sarib; Koko Komaruddin; Madiha Dzakiyyah Chairunnisa; Ahmad Labib Majdi; Sabil Mokodenseho (Sanskara Hukum dan HAM, 2023)
This qualitative research explores the role of Islamic law in shaping the identity and business ethics of Muslims in West Java, Indonesia. This research investigates how Islamic principles and cultural norms interact to influence ethical decision-making and identity formation among Muslim business owners. Through semi-structured interviews and document analysis, this research uncovers themes of integration between Islamic teachings and local customs, the impact of Islamic ethics on business behavior, the relationship between adherence to Islamic principles and self-identity, and the challenges faced in aligning religious obligations with economic reality. The findings highlight the synergy between religion and culture, the ethical foundation provided by Islamic principles, and strategies used to deal with challenges. The implications of this research include both theoretical understanding and practical application, offering insights for policy makers, business people, and religious leaders in promoting ethical and culturally sensitive business practices.